PENERAPAN NILAI-NILAI TRI HITA KARANA DALAM HUBUNGANNYA DENGAN BUDAYA ORGANISASI DI LINGKUNGAN POLITEKNIK NEGERI BALI - Ni Made Wirasyanti Dwi Pratiwi (Forum Manajemen STIMI Handayani Denpasar, 2016)
Research objectives are: (1) To determine a descriptive overview of theapplication of the values of Tri Hita Karana in the organizational culture in BaliState Polytechnic Environment; and (2) To determine the influence of the values ofTri Hita Karana in the organizational culture in Bali State Polytechnic environment.The study population were employees Bali State Polytechnic totaling 181 people.The sampling process is done by the proportionate stratified random sampling,with number of samples/respondents amounted to 93 people. This type of researchis an explanatory research. The technique of collecting data using questionnaires,interviews and observation.The results showed: (1) Variable parahyangan, pawonganand palemahan simultaneous influence of organizational culture amounted to 93.1%,Variable parahyangan partial effect on organizational culture by 26%, partialeffect pawongan of organizational culture by 2%, and partial effect palemahan oforganizational culture by 4.4 %; (2) The institution provides the opportunity foremployees to perform program tirta yatra, had a very good working environmentprovides opportunities for employees to demonstrate creativity and existence, andthe institution had programs related to preservation.